Essential Oil Variation within Warburgia salutaris–A Coveted Ethnomedicinal Aromatic Tree. Issue 11 (24th November 2020) - Leonard, Carmen; Kamatou, Guy; van Vuuren, Sandy; Sandasi, Maxleene; Viljoen, Alvaro
Abstract: Warburgia salutaris, known as 'Pepper bark', is an ethnomedicinally important tree found in the southern regions of Africa. A total of 75 fresh leaf specimens of W. salutaris ( n =40 wild and 35 cultivated) were collected from the Limpopo (wild) and KwaZulu‐Natal provinces (cultivated), two distinct locations in South Africa. In this study, the leaf essential oils obtained by hydrodistillation were characterized using gas chromatography coupled to mass spectrometry/flame ionization detection (GC/MS/FID). More than 15 compounds, accounting for 90–99 % of the total oil composition were identified. The analysis revealed that myrcene (0.6–65.3 %), ( E )‐β‐ocimene (nd–56.9 %), ( Z )‐β‐ocimene (nd–19.1 %), α‐pinene (nd–19.1 %) and limonene (nd–11.7 %) are major constituents of W. salutaris essential oils. Chemometric analysis revealed two major chemotypes within the essential oils with a modeled variation of approximately 60 %. Linalool and germacrene D were revealed as markers associated with the wild‐harvested oils, while cultivated oils were distinguished by higher levels of limonene and α‐humulene. The intra‐population variation indicated two chemically distinct chemotypes from three different populations, however, the season of harvest did not have a direct influence on the chemical profiles of the essential oils. Abstract :